Analisis Kinerja Layanan Pendidikan Sekolah Tinggi Ilmu Pertanian Berau Terhadap Persepsi Kepuasan Mahasiswa - Fitriah Agustika; Dony Obara; Sadrak Siregar; Ngakan Made Bayu Aditya; Vip Paramarta (International Forum of Researchers and Lecturers, 2024)
The aim of this research is to analyze the level of student satisfaction with the quality of services within the Berau College of Agricultural Sciences. From the results of observations and interviews, 5 variables were obtained, namely Lecturers, BAAK, Infrastructure, Lectures, and Image/Brand Image where the items in each measurement variable used the SERQUAL dimension. The sample of respondents was selected as 30 final semester students who had completed their thesis. The instrument was declared valid with a KMO value greater than the test value of 0.5 and reliable with a Cronbrach's Alpha value greater than the test value of 0.6 using SPSS 19. The results of the student satisfaction index (Customer Satisfaction Index) were 78.4%, which means The faculty is able to provide satisfactory quality services to students. From the science quadrant, it is found that Infrastructure and Lectures are in quadrant II (Presentation Priorities) where on average these variables are perceived as very important by students and the faculty has carried out a level of service performance in accordance with what students expect.